WebFRIS: An efficient web-based decision support tool to disseminate end-to-end risk information for flood management - Mohanty, Mohit Prakash; Karmakar, Subhankar (Journal of Environmental Management, 2021)

Assessment of socio-economic strategies for managing regional flood risk in an urban coastal catchment - Ghosh, Mousumi; Ghosh, Subimal; Karmakar, Subhankar (Urban Climate, 2024)

Flood management in India: A focussed review on the current status and future challenges - Mohanty, Mohit Prakash; Mudgil, Sahil; Karmakar, Subhankar (International Journal of Disaster Risk Reduction, 2020)

Identification of flood seasonality and drivers across Canada - Singh, Jitendra; Ghosh, Subimal; Simonovic, Slobodan P.; Karmakar, Subhankar (Hydrological Processes, 2021)
Abstract Floods are the most frequently occurring natural hazard in Canada. An in‐depth understanding of flood seasonality and its drivers at a national scale is essential. Here, a circular, statistics‐based approach is implemented to understand the seasonality of annual‐maximum floods (streamflow) and to identify their responsible drivers across Canada. Nearly 80% and 70% of flood events were found to occur during spring and summer in eastern and western watersheds across Canada, respectively. Flooding in the eastern and western watersheds was primarily driven by snowmelt and extreme precipitation, respectively. This observation suggests that increases in temperature have led to early spring snowmelt‐induced floods throughout eastern Canada. Our results indicate that precipitation (snowmelt) variability can exert large controls on the magnitude of flood peaks in western (eastern) watersheds in Canada. Further, the nonstationarity of flood peaks is modelled to account for impact of the dynamic behaviour of the identified flood drivers on extreme‐flood magnitude by using a cluster of 74 generalized additive models for location scale and shape models, which can capture both the linear and nonlinear characteristics of flood‐peak changes and can model its dependence on external covariates. Using nonstationary frequency analysis, we find that increasing precipitation and snowmelt magnitudes directly resulted in a significant increase in 50‐year streamflow. Our results highlight an east–west asymmetry in flood seasonality, indicating the existence of a climate signal in flood observations. The understating of flood seasonality and flood responses under the dynamic characteristics of precipitation and snowmelt extremes may facilitate the predictability of such events, which can aid in predicting and managing their impacts.

Tide-rainfall flood quotient: an incisive measure of comprehending a region’s response to storm-tide and pluvial flooding - Mohanty, Mohit Prakash; Sherly, Mazhuvanchery Avarachen; Ghosh, Subimal; Karmakar, Subhankar (Environmental Research Letters, 2020)
Abstract It is undeniable that coastal regions worldwide are facing unprecedented damages from catastrophic floods attributable to storm-tide (tidal) and extreme rainfall (pluvial). For flood-risk assessment, although recognizing compound impact of these drivers is a conventional practice, the marginal/individual impacts cannot be overlooked. In this letter, we propose a new measure, Tide-Rainfall Flood Quotient (TRFQ), to quantify the driver-specific flood potential of a coastal region arising from storm-tide or rainfall. A set of inundation and hazard maps are derived through a series of numerical and hydrodynamic flood model simulations comprising of design rainfall and design storm-tide. These experiments are demonstrated on three different geographically diverse flood-affected coastal regions in India. The new measure throws light on existing knowledge gaps on the propensity of coastal flooding induced by the marginal/individual contribution of storm-tide and rainfall. It shall prove useful in rationalizing long-term flood management strategies customizable for storm-tide and pluvial dominated global coastal regions.

Quantifying flood risks during monsoon and post-monsoon seasons: An integrated framework for resource-constrained coastal regions - Thakur, Dev Anand; Mohanty, Mohit Prakash; Mishra, Ashok; Karmakar, Subhankar (Journal of Hydrology, 2024)